FIRST CONODONTS FROM THE TRIASSIC OF THE SOUTHERN PAMIR REGION - Dagis A.A.; Dronov V.I. (My University, 1989)
Conodonts, one of the leading groups used for detailed stratigraphy, are rare in the Triassic deposits in the south of the USSR. In 1986 and 1987 the authors made a special search for conodonts in the Triassic of the Southeastern Pamirs. They studied the most promising sections in the Intermediate zone, which are characterized by basin faunas and containing, of the macrofauna, predominantly pelagic genera of bivalves (Posidonia, Daonella, Halobia), and also rare ammonoids. 12 levels with conodonts were distinguished in the Triassic deposits of the Southeastern Pamir, enabling these deposits to be correlated at the substage and zonal levels. This has substantially clarified the age of most of the formations and will make for more detailed and convincing correlations.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая